(3YeOI GdcJGH hYOI Phi GdCdHGHs - (3jhSa Hf YHO Gddg GdRLGLj, CHh GdbGSe,J (B415 (3g` s ((3jMi GdOjSWi Hf aNQ GdOjf Hf Ydi Hf TeS GdOjf eMeO GdeGdci s)
(3ChdgG (B:s
(3GdMeO ddg Cgd GdMeO heSJMbg CeG HYO CWGd Gddg HbGA ehdGfG GdQFjS aEfi JUaMJ GdCdaGX GdJi LeYgG bOGeI Hf LYaQ GdcGJH JNjQJ efgG eGUMJ eYGfjg hbUOJ Edi daXI de jhQO dgG bOGeI bQjfI aVeeJ EdjgG bQjfJgG s
(3BNQgG (B:s
(3hcTWJ LdOg Ci cTaJg hbTWg SdNg hcPdc jbGd cTW GdSMGH Yf GdSeGA Je GdcJGH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3GfXQ Qbe (B178 (3Yde dZI HYfhGf YeOI GdcGJHs
(3HChdgG JedcGf CbOegeG (B1340s
(3HgG fXGe GdJYbjHIs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GddZIs